PENGARUH POFITABILITAS, HUTANG, INTENSITAS KEPEMILIKAN ASET TERHADAP MANAJEMEN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2021 - Floppysta, Floppysta; Muid, Dul (Diponegoro Journal of Accounting, 2024)
This study aims to test the influence of profitability, debt, and asset ownership intensity on tax management in manufacturing companies listed on the IDX in 2019-2021. The variable used is the effective tax rate as a dependent variable. Profitability, debt, and intensity of asset ownership as independent variables.The population in this study is manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021 period. The data source used is secondary data derived from annual financial statements published through the official website of the Indonesia Stock Exchange and related companies. In this study, the researcher used the purposive sampling method in obtaining research samples. The number of samples used in this study is 6 companies with a total of 18 research data            The results of the study show that profitability, debt, and intensity of fixed asset ownership significantly affect the effective tax rate.